2020
DOI: 10.1186/s13018-020-01688-5
|View full text |Cite
|
Sign up to set email alerts
|

MiR-596 inhibits osteoblastic differentiation and cell proliferation by targeting Smad3 in steroid-induced osteonecrosis of femoral head

Abstract: Background: It is reported that miR-596 has a potential diagnostic value for non-traumatic osteonecrosis of the femoral head (NOFH), but its underlying mechanisms in NOFH is unclear. Methods: The expression of miR-596 and Smad3 was detected by western blot and quantitative real-time PCR. The relationship between the two molecules was explored using Dual-Luciferase Reporter Assay. Glucocorticoid (GC)dexamethasone, was used to induce bone marrow mesenchymal stem cell (BMSC) osteogenic differentiation, and the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…The findings revealed that miR-338-3p showed an opposite trend of expression in BMSCs with age and exerted negative functions on PCSK5, thereby limiting bone formation. Several studies also reported that an increasing number of miRNAs could regulate BMSC differentiation ( 31 33 ). In the present study, increased expression of miR-338-3p was observed in BMSCs of older rat samples, which indicated a counter-productive role of miR-338-3p in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that miR-338-3p showed an opposite trend of expression in BMSCs with age and exerted negative functions on PCSK5, thereby limiting bone formation. Several studies also reported that an increasing number of miRNAs could regulate BMSC differentiation ( 31 33 ). In the present study, increased expression of miR-338-3p was observed in BMSCs of older rat samples, which indicated a counter-productive role of miR-338-3p in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have disclosed that abnormal MSC differentiation leads to reduced osteogenic differentiation in ONFH patients [6]. In addition, accumulated evidence has demonstrated that many miRNAs, including miR-17-5p [9], miR-186-5p [10], miR-217 [11], and miR-596 [15] are involved in MSC differentiation in ONFH patients. In the current study, miR-423-5p levels were significantly increased in ONFH samples or during osteoblastic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Fu et al found that the expression of microRNA 596 ( miR-596) in the bone marrow of patients with steroid-induced femoral head necrosis (FHN) was upregulated, which could hinder the repair of the osteonecrotic bone by inhibiting the proliferation and osteogenic differentiation of the bone marrow stromal cells (BMSCs). 16 Some basic studies have found that microRNA-17-5p ( miR-17-5p ) and miR-210 are related to the pathogenesis of SANFH. 17 , 18 Du et al confirmed for the first time that four sensitive single-nucleotide polymorphisms (SNPs), namely, rs3740938, rs2012390, rs1940475, and rs11225395 of MMP8 from the MMP (matrix metalloproteinases)/TIMP (tissue inhibitors of MMP) system were significantly correlated with the increased risk of steroid-induced FHN in a study conducted in northern China.…”
Section: Mechanism Of Action Of Glucocorticoidsmentioning
confidence: 99%